Remarkable lives: Caitlin Jenkins in conversation with Jerome Carson. Issue 4 (4th November 2014) - Jenkins, Caitlin; Carson, Jerome
Abstract : Purpose: – The purpose of this paper is to offer a profile of Caitlin Jenkins. Design/methodology/approach: – Caitlin gives a short biographical account and is then interviewed by Jerome. Areas covered in the interview include her interest in psychiatric diagnosis, the helpfulness of counselling and personal narrative. Findings: – Caitlin believes that her recovery was only really possible when she was allowed to tell her own story, to be allowed the time and space to talk about events in her life. She mentions how psychodynamic therapy and CBT prevented her from truly exploring her personal story. Research limitations/implications: – While this is of course one person's account, it will find resonance with many others. Practical implications: – Reinforces the central role of narrative and its role in personal recovery. Social implications: – It stresses the importance of a truly therapeutic relationship. As Caitlin states, this enabled her to begin, "joining the dots of my experience to construct a meaningful personal narrative". Originality/value: – Counselling is often undervalued in contrast to more established therapies. This account demonstrates that what really matters to individuals recovering from mental health problems, is being listened to and being helped to make sense of their experiences.